Pandangan Teologi Tentang Teologi Reformasi dan Aplikasinya bagi Kekristenan Masa Kini - Paulus Kunto Baskoro (Jurnal Teologi (JUTEOLOG), 2021)
Theological view is a part that has always been the most important discussion and even debate in the history of the church. Because the theological viewpoint becomes a reference for building strength of standing in Christ Jesus. Strong theology will produce a perfect understanding of the truth of God's Word. However, it cannot be denied that in the development of God's church emerged developing theologies. One of them is the emergence of Reformed Theology. Those who are quite unsettled by previous theological developments, which are no longer in accordance with the truth of God's Word. Emerging reformers included Marthin Luther, Zwingli and Calvin. There are many doctrines that are being highlighted by the Reformed Theology group such as the doctrine of salvation, the Bible doctrine, the doctrine of God, water baptism and the Lord's Supper. This research uses descriptive method, which is studying Reformation Theology and its contribution to the historical understanding of contemporary theology. The author explores the truth in theological studies supported by historical facts and literature study literature studies. A complete discussion in the historical context of the emergence of Reformed Theology, the biblical basis for thinking about the emergence of Reformed Theology, personal views on the emergence of Reformed Theology, the church's views on the emergence of Reformed Theology, acceptance of the emergence of Reformed Theology at present, strengths and weaknesses of Reformed Theology In this section Reformed theology is studied theologically correct, so that some passages that are in accordance with Bible truth can be applied in the application of today's believers to become the basis for theological strength and spiritual growth to remain true to true Bible truth.